Blood indices of sheep fed with ensiled signal grass (Brachiaria decumbens) - Ahmad Fauzi, Nurul Aishah; Chung, Eric Lim Teik; Abu Bakar, Nurul Adilah; Kamalludin, Mamat Hamidi; Reduan, Mohd Farhan Hanif; Jesse, Faez Firdaus Abdullah; Dunshea, Frank R. (Taylor and Francis, 2025)
The Brachiaria species, particularly B. decumbens, is a key ruminant feed in the tropics but contains steroidal saponins that may cause toxicity, raising concerns for small ruminant farmers. Eighteen 6-month-old sheep were randomly assigned to three treatments over a 90-day feeding trial: Negative control (fresh P. purpureum), fresh B. decumbens, and positive control (ensiled B. decumbens). Blood samples were collected on days 0, 30, 60, and 90 for haematology and biochemistry analyses. Fresh B. decumbens group exhibited significantly elevated (p < 0.05) haematological parameters, including red and white blood cell counts, plasma protein, and various liver, kidney, and serum protein markers. In contrast, positive control group showed no significant differences (p > 0.05) compared to the negative control. Despite these variations, some values remained within normal ranges. The findings suggest that feeding ensiled B. decumbens mitigates the adverse effects of steroidal saponins, promoting overall healthier outcomes in sheep compared to fresh B. decumbens. Ensiling B. decumbens is a promising strategy to address saponin toxicity and improve ruminant feed safety.